At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.




5) 4(-87 + 4) 11 = 8(n - 3) - 1


Sagot :

-3652=8n-25
n=-453.375
So first I seperate both equations:
4(-87+4)
=-348+36
=-312

11=8(n-3)-1
= 11=8n-24-1
= 11=8n-25

Join them together and u get:
11=8n-25-312
= 11=8n-337
Move 11 to the right:
8n=-11-312
= 8n=-348
348/8n
=43.5n